El comportamiento de los gastos del presupuesto en el Gobierno Autónomo Descentralizado Parroquial Rural de La Unión durante el período 2023. - Fernández Mancilla, Roxanna Nereyda (2024)
In the analysis of the behavior of the budget expenditures of the Rural Decentralized Autonomous Parish Government of La Unión during the period 2023, several critical areas are identified that require attention. The comparison between the initial budget and the actual execution shows a notable discrepancy. Total revenues and transfers executed in 2023 were significantly lower than the initial budget estimates. This difference reveals errors in revenue estimation and expenditure planning, highlighting the need to improve projection techniques and conduct more rigorous analysis to adjust budget forecasts. Efficiency in the management of transfers and investments also experienced a considerable drop, suggesting problems in project implementation and fund management. A detailed analysis of expenditure execution processes is essential to identify and address areas with inefficiencies. This will allow for optimization of resource allocation and ensure that funds are used more effectively, with the aim of meeting established budget objectives. Furthermore, the significant variation in budget efficiency between the years 2022 and 2023 underlines the need to stabilize the budget to avoid extreme fluctuations. The drastic reduction in actual execution compared to the initial budget indicates an instability in budget planning and execution. To achieve greater financial stability and more predictable budget execution, it is essential to implement stricter control mechanisms and conduct periodic reviews of budget performance. These measures will contribute to a more solid financial management aligned with the economic reality of the parish government.